A Comparison on Similarity Distances and Prioritization Techniques for Early Fault Detection Rate - Abd Razak, Safwan; Isa, Mohd Adham; Abang Jawawi, Dayang Norhayati (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
Nowadays, the Software Product Line (SPL) had replaced the conventional product development system. Many researches have been carried out to ensure the SPL usage prune the benefits toward the recent technologies. However, there are still some problems exist within the concept itself, such as variability and commonality. Due to its variability, exhaustive testing is not possible. Various solutions have been proposed to lessen this problem. One of them is prioritization technique, in which it is used to arrange back the test cases to achieve a specific performance goal. In this paper, the early fault detection is selected as the performance goal. Similarity function is used within our prioritization approach. Five different types of prioritization techniques are used in the experiment. The experiment results indicate that the greed-aided-clustering ordered sequence (GOS) shows the highest rate of early fault detection.